PENGARUH BUDAYA ORGANISASI, MOTIVASI KERJA DAN GAYA KEPEMIMPINAN TRANSFORMASI TERHADAP KEPUASAN KERJA ASN SERTA KINERJA ASN DI DINAS PETERNAKAN DAN PERIKANAN KABUAPTEN SITUBONDO - Nofiantari, Efi; Karnadi, Karnadi; Pramesthi, Riska Ayu (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
Human resources are one of the important factors in a company to achieve its goals and objectives, because human resources are one of the determining factors for the success or failure of a company in achieving its goals. One that must be considered in managing human resources is regarding the placement of employees. The aim of this study was to determine the effect of organizational culture, work motivation and transformational leadership style on ASN job satisfaction and ASN performance in the Livestock and Fisheries Service of Situbondo District. the population in this study were all ASN employees of the Situbondo District Livestock and Fisheries Service. Random sampling method (simple probability sampling) without regard to strata in the population in this study. In taking this sample using saturated sampling, namely the technique of determining the sample when all members of the population are sampled. Data analysis and hypothesis testing in this study used the Structural-partial Least square equation model (PLS-SEM). The results of the hypothesis test have a direct effect using the smart PLS 3.0 application, indicating that organizational culture has a significant positive effect on job satisfaction. Work motivation has a significant positive effect on job satisfaction. Transformational leadership style has a significant positive effect on job satisfaction. Organizational culture has a significant positive effect on performance. Work motivation has a significant positive effect on performance. Transformational leadership style has no significant positive effect on performance. Job satisfaction has a significant positive effect on performance. Organizational culture on performance through job satisfaction has no significant positive effect. Work motivation on performance through job satisfaction has a significant positive effect. Transformational leadership style on performance through job satisfaction has a significant positive effect.